Social Learning Through Endogenous Information Acquisition: An Experiment - Çelen, Boğaçhan; Hyndman, Kyle (Management Science, 2012)
This paper provides a test of a theory of social learning through endogenous information acquisition. A group of subjects face a decision problem under uncertainty. Subjects are endowed with private information about the fundamentals of the problem and make decisions sequentially. The key feature of the experiment is that subjects can observe the decisions of predecessors by forming links at a cost. The model predicts that the average welfare is enhanced in the presence of a small cost. Our experimental results support this prediction. When the informativeness of signals changes across treatments, behavior changes in accordance with the theory. However, within treatments, there are important deviations from rationality such as a tendency to conform and excessive link formation. Given these biases, our results indicate that subjects would, except when faced with a small cost, have been better off not forming any links. This paper was accepted by Teck Ho, behavioral economics.